Dosimetric benefits of gantry‐static couch‐motion (GsCM) technique for breast boost radiation therapy: Reduced dose to organs‐at‐risk and improved dosimetric indices. Issue 9 (5th July 2020) - Gill, Gurtej S.; Jakubovic, Raphael Y.; Baker, Jameson; Button, Terry; Chang, Jenghwa
Abstract: To evaluate the clinical feasibility and dosimetric benefits of a novel gantry‐static couch‐motion (GsCM) technique for external beam photon boost treatment of lumpectomy cavity in patients with early‐stage breast cancer in comparison to three‐dimensional conformal radiotherapy (3D‐CRT), wedge pair in supine position (WPS), and wedge pair in decubitus position (WPD) techniques. A retrospective review was conducted on breast patients (right breast, n = 10 and left breast, n = 10) who received 10 Gy boost after 50 Gy to whole breast. The treatment plans were generated using an isocentric‐based GsCM technique (a VMAT type planning approach) integrating couch rotational motion at static gantry positions. Static fields for each tangential side were merged using a Matlab ® script and delivered automatically within the Varian Truebeam TM STx in Developer Mode application as a VMAT arc (wide‐angular medial and short‐angular lateral arcs). The dosimetric accuracy of the plan delivery was evaluated by ion chamber array measurements in phantom. For both right and left breast boost GsCM, 3D‐CRT, WPS, and WPD all provided an adequate coverage to PTV. GsCM significantly reduced the ipsilateral lung V30% for right side (mean, 80%) and left side (mean, 70%). Heart V5% reduced by 90% (mean) for right and 80% (mean) for left side. Ipsilateral breast V50% and mean dose were comparable for all techniques but for GsCM, V100% reduced by 50% (mean) for right and left side. The automated delivery of both arcs was under 2 min as compared to delivering individual fields (30 ± 5 min). The gamma analysis using 2 mm distance to agreement (DTA) and 2% dose difference (DD) was 98 ± 1.5% for all 20 plans. The GsCM technique facilitates coronal plane dose delivery appropriate for deep‐seated breast boost cavities, with sufficient dose conformity of target volume paired with sparing of the OARs.